Conducting Qualitative Research to Respond to COVID-19 Challenges: Reflections for the Present and Beyond. (12th April 2021) - Tremblay, Stephanie; Castiglione, Sonia; Audet, Li-Anne; Desmarais, Michèle; Horace, Minnie; Peláez, Sandra
The global response to mitigate the spread of the COVID-19 pandemic brought about massive health, social and economic impacts. Based on the pressing need to respond to the crisis, clinical trials and epidemiological studies have been undertaken, however less attention has been paid to the contextualized experiences and meanings attributed to COVID-19 and strategies to mitigate its spread on healthcare workers, patients, and other various groups. This commentary examines the relevance of qualitative approaches in capturing deeper understandings of current lived realities of those affected by the pandemic. Two main challenges associated with the development of qualitative research in the COVID-19 context, namely "time constraints" and "physical distancing" are addressed. Reflections on how to undertake qualitative healthcare research given the evolving restrictions are provided. These considerations are important for the integration of qualitative findings into policies and practices that will shape the current response to the pandemic and beyond.